Dynamics of Building Function Changes in Urban Areas of Binjai City - Ruzham Ruzham; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Changes in building functions in urban areas have become an inevitable phenomenon, especially in developing cities such as Binjai City. This study aims to analyze the factors influencing building function changes in the area, using a Mixed Methods approach that combines quantitative analysis through multiple linear regression and qualitative documentation based on field observations. Four independent variables were examined: inconsistency with the Spatial Plan (RTRW), accessibility, economic motivation, and law enforcement.The results show that economic motivation and accessibility have a significant influence on building function changes. Meanwhile, the variables of RTRW inconsistency and weak law enforcement did not show statistically significant effects. These findings are supported by visual field evidence indicating a massive conversion of building functions without effective spatial planning control. Photographic documentation reveals a tendency among the community to adapt building functions for economic activities in strategically accessible areas.The study concludes that building function changes in Binjai City are driven by economic needs and urban spatial dynamics that are not matched by supervision and enforcement of spatial planning regulations. Recommendations include strengthening spatial supervision, providing socio-economic-based incentives, simplifying permit processes, and implementing community-based public education. This research offers valuable contributions to adaptive urban planning while upholding the principles of spatial order and community aspirations.